The Effect of Climate Change on Agricultural Production among Farmers in Kwali Area Council of Federal Capital Territory of Nigeria - Aregbesola, Busayo Gbemisola; Ebele, F. U.; Haastrup, D.T.; Adams, E. (Advances in Social Sciences Research Journal, 2014)
This study examined the effects of climate change on agricultural production among farmers in Kwali Area Council of the Federal Capital Territory, Abuja Nigeria. A total of 150 farmers from every community in the Area Council were randomly selected. The main instrument used in this research work is questionnaire which consist of twenty-one different questions to identified the issues on climate change in the area council including the intervention they have enjoyed so far from the government. The instrument was validated by having one climate expert, one lecturer from Department of Science & Environmental Education University of Abuja and one lecturer from Department of Agriculture Science Federal University of Technology Minna State (FUT). Data collated for the study were analyzed using frequency counts and mean statistics. Results of the descriptive analysis demonstrate that rise in temperature, solar radiation, low rainfall and the presence of excessive of nitrogen as a result of climate change are affecting agricultural production in Kwali Area Council. Thus, there is need for immediate intervention to save future production of food from this area council, also to help provide jobs for their youth since farming is their major occupation and to protect their farmlands from losing vital nutrients which can support agricultural production.